Public Feminisms : From Academy to Community - Dove-Viebahn, Aviva; Baker, Carrie N.; Michigan Publishing (University of Michigan); Project Muse. (Amherst, Massachusetts : Lever Press, 2022)
A city walking tour that subverts tourists$1 (Bassumptions about sex workers. Collaborative performances that offer participants a way to understand the stories of disappeared and murdered Indigenous women. Testimony before a state legislature on the harmful impact of parental consent laws for minors seeking abortion health care. A public film and discussion series encouraging intersectional feminist analysis. A Writing Center employing a Black feminist approach to teach writing to community members. These are just some of the stories told in this volume. Through art and public programming, activism and policy advocacy, public writing and community education, feminists in higher education are using scholarly methods and pedagogies to share academic knowledge and research with their communities at the local, national and international levels. These scholars are advancing public knowledge about issues affecting women and girls, racial and ethnic minorities, immigrants, Indigenous peoples, LGBTQAI individuals, and others facing discrimination, lacking resources, or experiencing economic, political and social injustices. This book offers a selection of case studies, models, narratives and tools from a diverse array of writers whose essays the editors have carefully curated to showcase myriad strategies for community engagement. Accessible and engaging to a broad range of readers, the essays in this volume are a rich resource for scholars interested in infusing their academic knowledge into the public sphere. This volume offers an opportunity to reflect on the meaning and importance of community engagement for scholars, and archives some of the important public-facing work feminists are doing today.s
Description based on print version record.
Keywords: Women's rights; Women -- Social conditions; Women -- Education (Higher) -- Social aspects; Feminism and higher education; Women -- Social conditions -- 21st century; Women's rights; Women -- Education (Higher) -- Social aspects; Feminism and higher education; Electronic books